PENGARUH PENGETAHUAN PAJAK DAN TINGKAT PENGHASILAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR PADA KELURAHAN BEKASI JAYA - Gatot Hery Djatmika; Budi Harsono; Rosidah Rosidah; Yohanes Bowo Widodo (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
This study aims to examine and analyze the influence of tax knowledge and income levels on taxpayer compliance in paying motor vehicle taxes in the area of Bekasi Jaya, East Bekasi. The data was collected through questionnaires and conducted on 100 respondents residing in the area of Bekasi Jaya Urban Village, East Bekasi. Data analysis in this study using SPSS version 22. The analysis technique used is multiple regression analysis with the least squares equation and hypothesis test using t-statistics to test the partial regression coefficient with level of significance 5%. In addition, the validity test, reliability test, and classic assumption test include normality test, multicollinearity test, and heteroscedasticity test. The results showed that: (1) There is a positive and significant influence between tax knowledge with taxpayer compliance t value> t table (6,709> 1,66) and significance <0,05 (0,000 <0,05), Ho is rejected. (2) There is a significant positive influence between income level with taxpayer compliance, t count> t table (6,917>1,66) and significance <0,05 (0,000 <0,05), Ho is rejected. Based on the results of research are not found variables that deviate from the classical assumption, it shows that the available data have been qualified to use multiple linear regression equation model. From the results of research indicates that taxpayer compliance and income level have a positive effect on taxpayer compliance. The predictive ability of both variables on taxpayer compliance is 70.1%.